Musical Expertise and Statistical Learning of Musical and Linguistic Structures - Francois, Clément; Schön, Daniele (Frontiers in Psychology, 2011)
Adults and infants can use the statistical properties of syllable sequences to extract words from continuous speech. Here we present a review of a series of electrophysiological studies investigating 1) Speech segmentation resulting from exposure to spoken and sung sequences 2) The extraction of linguistic versus musical information from a sung sequence3) Differences between musicians and nonmusicians in both linguistic and musical dimensions. The results show that segmentation is better after exposure to sung compared to spoken material and moreover, that linguistic structure is better learned than the musical structure when using sung material. In addition, musical expertise facilitates the learning of both linguistic and musical structures. Finally, an electrophysiological approach, which directly measures brain activity, appears to be more sensitive than a behavioral one.